2009
DOI: 10.1111/j.1399-3054.2008.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and labeling methods for microarrays using small amounts of plant tissue

Abstract: Procedures were developed to maximize the yield of high-quality RNA from small amounts of plant biomass for microarrays. Two disruption techniques (bead milling and pestle and mortar) were compared for the yield and the quality of RNA extracted from 1-week-old Arabidopsis thaliana seedlings (approximately 0.5-30 mg total biomass). The pestle and mortar method of extraction showed enhanced RNA quality at the smaller biomass samples compared with the bead milling technique, although the quality in the bead milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Tissues from shoots only were used for this study. Tissue of shoots was disrupted in a microcentrifuge tube using a Pellet Pestle motor (Kontes, Vineland, New Jersey, USA) and sterile RNase‐free pestle tip (Stimpson et al, 2009). Extraction was conducted using the RNeasy Mini Plant Kit (Qiagen, Valencia, CA) according to the procedure outlined in the RNeasy Mini Handbook.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissues from shoots only were used for this study. Tissue of shoots was disrupted in a microcentrifuge tube using a Pellet Pestle motor (Kontes, Vineland, New Jersey, USA) and sterile RNase‐free pestle tip (Stimpson et al, 2009). Extraction was conducted using the RNeasy Mini Plant Kit (Qiagen, Valencia, CA) according to the procedure outlined in the RNeasy Mini Handbook.…”
Section: Methodsmentioning
confidence: 99%
“…Seedlings were shipped overnight on dry ice from −80°C storage at the University of Florida and placed in −80°C storage upon arrival. Seedlings were defrosted, then dissected in RNAlater, disrupted using a pellet pestle motor and sterile pestle, and RNA was extracted from the shoots using the RNeasy Mini Plant Kit (Qiagen, Valencia, California, USA), according to the procedure outlined previously (Stimpson et al, 2009). Following extraction, excess fluid was evaporated using a centrifugal vacuum evaporator Savant Speed Vac Concentrator (Thermo Scientific, Waltham, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Results from the cytological and gene profiling studies will be reported in future publications; the methods used were similar to those utilized in our previously published papers (Guisinger and Kiss, 1999;Yamamoto and Kiss, 2002;Stimpson et al, 2009).…”
Section: Postflight Recovery Of Samples and Processingmentioning
confidence: 99%
“…; Stimpson et al . ). Several operation products must be developed, and integration testing is part of the experiment integration phase.…”
Section: Preparation For and Performance Of An Emcs Experimentsmentioning
confidence: 97%
“…These tests often produce valuable information, worth making available to other scientists and engineers preparing for future space experiments (e.g. Correll et al 2005;Kiss et al 2007;Stimpson et al 2009). Several operation products must be developed, and integration testing is part of the experiment integration phase.…”
Section: Preparation For and Performance Of An Emcs Experimentsmentioning
confidence: 99%